L’incidence de la rente publique sur l’épargne privée : un survol de la littérature théorique et empirique - Rousseau, Henri-Paul (L'Actualité économique, 1978)
This paper provides a survey of the literature on the effect of public pension funds on private savings. Both theoretical and empirical studies are discussed within a simple theoretical frame-work. The survey concludes that private saving is probably negatively influenced by public pension funds but that the magnitude of the effect is uncertain.